2004
DOI: 10.1038/modpathol.3800197
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of a p63/α-methyl-CoA-racemase (p504s) cocktail in atypical foci in the prostate

Abstract: Prostatic needle biopsy is the preferred method for diagnosing early prostate cancer, providing specific information. In cases of histological cancer mimics, a diagnosis of atypical small acinar proliferation suspected of but not diagnosed as malignancy can be made. In such cases, and in small focus carcinomas, pathologists use 34bE12, cytokeratin (CK) 5/6 or p63 immunostaining to label basal cells, and a-methylacyl-CoA racemase (AMACR/p504s) immunostaining as a positive prostate cancer marker on two distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 30 publications
6
68
0
10
Order By: Relevance
“…At an estimated cost of $31.00 per immunostain, the average COMMENT The diagnostic utility of HMWK and AMACR have been evaluated extensively in the prostate pathology practice from a diagnostic perspective, but the quality assurance and the cost aspects of the use of IHC in evaluating prostate needle biopsies, a large segment of genitourinary pathology practice, to our knowledge have not been previously addressed. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] It is uncertain, for example, how much IHC is used in routine prostate biopsy practice; what is the appropriate level of IHC use, both from diagnostic and quality assurance purposes; what is the breakdown of the final diagnostic decisions when IHC is used; what are the implications for additional departmental consultations; and what are the associated costs of the use of IHC? Some of these issues, such as the level and the suitability of IHC use in evaluating prostate needle biopsies, are obviously influenced by additional factors, including the type of practice (academic/teaching versus private; general versus specialized; community versus consult), pathologist's level of experience, expertise, and the volume of prostate biopsy material seen, as well as the quality of the produced slides, which may be dependent on the tissue fixation, the thickness of the sections, and the staining quality of the slides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At an estimated cost of $31.00 per immunostain, the average COMMENT The diagnostic utility of HMWK and AMACR have been evaluated extensively in the prostate pathology practice from a diagnostic perspective, but the quality assurance and the cost aspects of the use of IHC in evaluating prostate needle biopsies, a large segment of genitourinary pathology practice, to our knowledge have not been previously addressed. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] It is uncertain, for example, how much IHC is used in routine prostate biopsy practice; what is the appropriate level of IHC use, both from diagnostic and quality assurance purposes; what is the breakdown of the final diagnostic decisions when IHC is used; what are the implications for additional departmental consultations; and what are the associated costs of the use of IHC? Some of these issues, such as the level and the suitability of IHC use in evaluating prostate needle biopsies, are obviously influenced by additional factors, including the type of practice (academic/teaching versus private; general versus specialized; community versus consult), pathologist's level of experience, expertise, and the volume of prostate biopsy material seen, as well as the quality of the produced slides, which may be dependent on the tissue fixation, the thickness of the sections, and the staining quality of the slides.…”
Section: Resultsmentioning
confidence: 99%
“…The use of IHC for highmolecular-weight keratin (HMWK) and a-methylacyl coenzyme A racemase (AMACR), either individually or in combination, has been studied extensively in prostate pathology practice, primarily as a tool in confirming and establishing cancer diagnosis on prostate needle biopsy and for evaluating challenging and questionable foci in prostate specimens, particularly on needle biopsy. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In addition, IHC use has risen for the evaluation of prostate needle biopsies because its use in conjunction with morphology is critical to prevent diagnostic errors, especially diagnostic overcalls that may lead to unnecessary radical prostatectomy. Indeed, the use of IHC in prostate biopsy has shown an upward trend over time.…”
mentioning
confidence: 99%
“…The up-regulation of AMACR in atrophic prostate, PIN, localized and metastatic prostate cancer was further confirmed at the protein level [220,221]. Due to its consistent over-expression in prostate cancer, AMACR is now considered an excellent molecular marker for prostate cancer and has been widely investigated in clinical diagnosis, with both high sensitivity and specificity [220,[225][226][227][228][229].…”
Section: Amacr and Prostate Cancermentioning
confidence: 95%
“…The most relevant markers of papillary RCC are vimentin and CK7 [17]. More recently, alphamethyl CoA racemase (AMACR), a peroxymal mitochondrial enzyme involved in the b-oxidation of branched-chain fatty acids and fatty acid derivatives, identified as a molecular marker for prostate cancer [18][19][20][21] on the basis of complementary (cDNA) microarray technology, has also been reported in epithelial tumors [22][23][24] and in kidney cancers [16,25]. Complementary DNA microarray study has demonstrated that AMACR overexpression in papillary RCC is one of the top 10 most highly expressed genes [26,27].…”
Section: Introductionmentioning
confidence: 99%